Serological tests fail to discriminate dogs with visceral leishmaniasis that transmit Leishmania infantum to the vector Lutzomyia longipalpis - Ivete Lopes de Mendonça; Joilson Ferreira Batista; Guilherme Loureiro Werneck; Maria Regiane Araújo Soares; Dorcas Lamounier Costa; Carlos Henrique Nery Costa (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION The control of reservoirs for Leishmania infantum -induced zoonotic visceral leishmaniasis requires the identification of dogs posing a population risk. Here, we assessed the performance of several assays to identify Lutzomyia longipalpis infectious dogs. METHODS We evaluated 99 dogs that were positive for visceral leishmaniasis based on parasite identification. Serological analyses were performed using an enzyme-linked immunosorbent assay, immunofluorescence antibody tests in 1:40 and 1:80 dilutions, rapid dual path platform tests, immunochromatographic assay with a recombinant rK39 antigen, fast agglutination screening tests, and direct agglutination tests. We also performed PCR to analyze peripheral blood and xenodiagnosis. RESULTS Forty-six dogs infected at least one L. longipalpis specimen. Although the serological test sensitivities were above 85% for detecting L. longipalpis infectious dogs, none showed a satisfactory performance, as both specificity (0.06 to 13%) and the area under the receiver operating characteristic curve (45 to 53%) were low. The PCR results were also weak, with a sensitivity of 30%, specificity of 72%, and an area under the receiver operating characteristic curve of 51%. The infected L. longipalpis proportion was higher among asymptomatic dogs than symptomatic dogs. Among the symptomatic dogs, those with ulceration-free skin diseases were more infectious, with an odds ratio of 9.3 (confidence interval of 1.10 - 428.5). The larger the number of insects fed, the greater the detected infectiousness. CONCLUSIONS Our study supports the imperative to develop novel technologies for identifying the infectious dogs that transmit L. infantum for the benefit of public health.